О находке вечерницы малой в Закарпатской области УССР - Абеленцев, В.И. (Вестник зоологии, 1967)
For the first time the author discovered Nyctalus leislery KuhI. in Transcarpathian region, in beech forests near the village of Malaya Ugolka of Tyachev district. The animal was caught by a capron «web-like» net for catching small birds on the 20-th of May, 1965, at 21.30 p. m. during food-procuring flights of chiropterae. Measuring and craniometry indices and internal organ weight are presented. The carcass is kept in the fond collections of the museum of the Institute of Zoology of the Ukrainian Academy of Sciences.